Bio-Waste Corn–cob Cellulose Supported Poly(amidoxime) Palladium Nanoparticles for Suzuki-Miyaura Cross-Coupling Reactions - Sultana, Tahnim; Mandal, Bablu Hira; Lutfor, M. R.; Sarkar, Shaheen M. (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2016)
Waste corn-cob cellulose supported poly(amidoxime) palladium nanoparticles (PdNs@PA) were prepared by the surface modification of waste corn-cob cellulose through graft co-polymerization and subsequent amidoximation. The supported nanoperticles showed high catalytic activity (45-400 mol ppm) towards Suzuki-Miyaura cross-coupling of aryl bromides/chlorides with organoboronic acids to give the corresponding biaryl products up to 99% yield with high turnover number (TON) 19777 and turnover frequency (TOF) 4944 h-1. The PdNs@PA was easily recovered from the reaction mixture and reused several times without significant loss of its catalytic activity